Mass lesions of ovary - Tumor markers can be misleading - Savithri, Moothiringode Chitrabhanu; Abraham, Usha Mary (Asian Journal of Medical Sciences, 2014)
Background: Ovarian mass lesions could be neoplastic or non neoplastic. The less aggressive lesions should be distinguished from carcinomas which require extensive surgical procedures. CA-125 is a tumor marker used for evaluating ovarian carcinomas. In this series we found seven cases of sex cord stromal tumors (SCT) and endometriotic cysts with raised CA-125 levels, the highest value being 1540 IU/ml. Aims and Objectives: 1) To retrospectively evaluate cases which presented as mass lesions of ovary over a two year period along with CA-125 levels if available. 2) To find out the number of non carcinomatous lesions with elevation of the tumor marker CA-125. Materials and Methods: Total number of ovarian tumors and endometriotic cysts reported in the Department of Pathology, Amala Institute of Medical Sciences, Thrissur, Kerala, India in the two year period of 2012 and 2013 were retrospectively identified. CA-125 levels if available were noted. Results: Primary ovarian tumors comprised 180 cases, the rest being metastastic adenocarcinomas. There were 15 cases of SCT and 21 endometriotic cysts. CA 125 levels were increased in 2 cases each of granulosa cell tumors and fibrothecomas and 3 cases of endometriotic cysts. Highest value was 1540 IU/ml. Conclusion: Elevation of the tumor marker CA 125 often tricks the clinician into making a provisional diagnosis of carcinoma of ovary. It is important to understand the limitations in the interpretation of tumor markers so that more aggressive treatment modalities are avoided. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10983 Asian Journal of Medical Sciences Vol.6(3) 2015 26-29